Transcriptional Analysis of C-Repeat Binding Factors in Fruit of Citrus Species with Differential Sensitivity to Chilling Injury during Postharvest Storage - Matías Salvo (International Journal of Molecular Sciences, 2021)
Citrus fruit are sensitive to chilling injury (CI) during cold storage, a peel disorder that causes economic losses. C-repeat binding factors (CBFs) are related to cold acclimation and tolerance in different plants. To explore the role of Citrus CBFs in fruit response to cold, an in silico study was performed, revealing three genes (CBF1, CBF2, and CBF3) whose expression in CI sensitive and tolerant cultivars was followed. Major changes occurred at the early stages of cold exposure (1–5 d). Interestingly, CBF1 was the most stimulated gene in the peel of CI-tolerant cultivars (Lisbon lemon, Star Ruby grapefruit, and Navelina orange), remaining unaltered in sensitive cultivars (Meyer lemon, Marsh grapefruit, and Salustiana orange). Results suggest a positive association of CBF1 expression with cold tolerance in Citrus cultivars (except for mandarins), whereas the expression of CBF2 or CBF3 genes did not reveal a clear relationship with the susceptibility to CI. Light avoidance during fruit growth reduced postharvest CI in most sensitive cultivars, associated with a rapid and transient enhance in the expression of the three CBFs. Results suggest that CBFs-dependent pathways mediate at least part of the cold tolerance responses in sensitive Citrus, indicating that CBF1 participates in the natural tolerance to CI.